Chinese Indonesian Cultural and Religious Diplomacy - Rohman, Abid (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2019)
This paper aims to find out the cultural and religious influences and their opportunities and challenges in the Chinese-Indonesian public diplomacy perspective. This study uses a qualitative-descriptive approach by taking literature review as main source of data, and interviews with several religious leaders and community leaders related as secondary sources. The author finds that culture and religion have influenced the practice of Chinese-Indonesian public diplomacy (in terms of art, culture, tradition and practice of diplomacy). Admiral Cheng Hoo holds major roles in the spread of Islam that time. The roles of non-state actors are crucial when conducting people-to-people approach: as dialogue and cooperation partner, and as promotor.